MORPHOLOGIC VARIATION IN PNEUMOCOCCUS : I. AN ANALYSIS OF THE BASES FOR MORPHOLOGIC VARIATION IN PNEUMOCOCCUS AND DESCRIPTION OF A HITHERTO UNDEFINED MORPHOLOGIC VARIANT - Austrian, Robert (The Rockefeller University Press, 1953)
The problem of morphologic variation in pneumococcus has been reviewed and the desirability of studying such variation through an examination of bacterial cells rather than of bacterial colonies has been pointed out. To further this objective, a new terminology to describe the morphologic variants of pneumococcus, potentially applicable to other bacterial species, has been proposed. A hitherto undefined morphologic variant of pneumococcus, the filamentous capsulated (fil+ S+) variant, has been defined and its relationship to the three previously recognized non-filamentous capsulated (fil- S+), nonfilamentous non-capsulated (fil- S-), and filamentous non-capsulated (fil+ S-) variants has been presented.